Teaching Araling Panlipunan: A Study of Challenges and Coping Mecha-nisms among Non-Social Studies Major Educators - David, Rowena May T. (Future Science / FSH-PH Publications, 2024)
This research focused on the challenges and coping mechanisms of Non-Social Studies major teachers assigned to teach Araling Panlipunan in Bulacan, Philippines. This, therefore, makes the pressing call for comprehensive content knowledge, effective assessment strategies, collaborative approaches to teaching, and continuous professional development in order to fill the gap in expertise in teaching Philippine history, culture, and society. Key findings revealed that teachers belonging to the Non-Social Studies major often experience problems in their teaching brought about by insufficient subject-specific knowledge, which consequently affects their confidence and accuracy in content delivery. In this regard, it is proposed in the study a program on